Lateral earth pressures acting on circular shafts considering soil-structure interaction. Issue 2 (4th March 2019) - Chehadeh, Ali; Turan, Alper; Abed, Farid; Yamin, Mohammad
Abstract: Nowadays, there is a significant demand on developing and expanding the existing infrastructure which necessitates the implementation of fast and cost effective construction methods such as the secant pile walls. The secant pile walls constructed in a circular plan layout to form a vertical shaft provide unique advantages such as compression ring behaviour. Compression rings act as a single-unit system in resisting lateral earth pressure and converting loads from all directions to compressive forces which can be resisted only by low concrete strength. Secant pile walls require stringent drilling tolerances to be achieved in order to behave as a compression ring and to perform as an effective groundwater cut-off wall. This paper presents a parametric study that investigates various aspects of the behaviour of circular shafts constructed using secant pile walls. The aspects that are studied include the identification of the magnitude and distribution of earth pressures exerted on circular shafts by the retained material. The distribution of surcharge pressures on the shaft walls is also studied. The results showed that the surcharge pressures on the wall increased with increasing width of surcharge area; for example, the maximum surcharge pressure increased by at least 60% when surcharge width increased from W = 3 m to W = 48 m. In addition, the results indicated a decrease of the maximum surcharge pressure on the wall by almost 22% when shaft radius decreased from R = 5 m to R = 3 m for Soil 1. Unlike what is observed in plane strain conditions, distance between the surcharge and shaft wall was seen to have a small effect on the magnitude of maximum pressures. The results also showed that the theoretical estimate of pressures underestimated the calculated values at larger depths and that the horizontal extent of the spread of pressure around the shaft was significantly influenced by the type of soil as well as width of surcharge. The outcomes of this study address practical design concerns and are considered to be of interest to those involved in design and construction of vertical shafts.